Celebrating Christine Watkins' 29th Birthday - Watkins, Howard::::::::: (1978)
Tom Shilton, Christine Watkins, ?, Dianne Shilton, Marilyn Osganian, Don Leet, ?, ?, ?, Peggy Wilson Eating dinner in living room